« Fonction exponentielle/Croissances comparées » : différence entre les versions

m (Robot : Remplacement de texte automatisé (- *\| *niveau *= * + | niveau = ))
<math>\lim\limits_{x\to-\infty} xe^x= \lim\limits_{x\to-\infty} \dfrac{x}{e^{-x}}= -\lim\limits_{x\to-\infty} \dfrac{-x}{e^{-x}}</math>
 
En posant <math>t=-x</math>, on a <math>-\lim\limits_{x\to-\infty} \dfrac{-x}{e^{-x}}= - \lim\limits_{t\to -+\infty} \dfrac{t}{e^{t}}=- \lim\limits_{t\to -+\infty} \dfrac{1}{\dfrac{e^t}{t}}=0</math>
 
== Application ==
Utilisateur anonyme